Measurement of the polarisation of single top quarks and antiquarks produced in the t-channel at s $$ \sqrt{s} $$ = 13 TeV and bounds on the tWb dipole operator from the ATLAS experiment. (Tufts University. Tisch Library., 2022)
Keywords : Hadron-Hadron Scattering, Top Physics.; Springer Open.